If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+2=6x+4=12x-4
We move all terms to the left:
5x+2-(6x+4)=0
We get rid of parentheses
5x-6x-4+2=0
We add all the numbers together, and all the variables
-1x-2=0
We move all terms containing x to the left, all other terms to the right
-x=2
x=2/-1
x=-2
| -2(3x+10)=4+(x-7) | | 19n−17n=12 | | 2x+45=3.5x-60 | | 6x-12=10x+8 | | 14+3x=80 | | -89=-3(x+4)-8x | | –6x+5=17 | | 3.6w=1.6+27 | | 35x-9876=0 | | 24n-3=1.5 | | 6x-12=80 | | 2(6x+38)=62-2x | | 44+x=91 | | 2(4x+5)=25-2x | | 28=4(y+4)-8y | | -0.75w-8=-2 | | 1.5n+3=24 | | 4.5n+3+(-2.3n)-8=3 | | 8000=-0.012t-0.24t^2+6.3 | | -51x(6-1)=0 | | 7x2=847 | | 3n+1.5=24 | | 10x-8+10x-8+136=180 | | 8x–19=13 | | -1/2x-6=14 | | -18n=-27 | | 1.5+3n=24 | | 15x-31=9x | | 8x+1/3=4x+3/2 | | 2x+4+x=36 | | 8x+1/3=4 | | 2x=4(10-x)-2 |